The Rapid Changes of the Landscape Structure of the Meranti-Dangku Tropical Lowland Forest in the South Sumatra Province, Indonesia - Zulfikhar Zulfikhar; Hilda Zulkifli; Sabaruddin Kadir; Iskhaq Iskandar (Program Pascasarjana Universitas Sriwijaya, 2017)
The fragmentation of forest vegetation cover can be measured quantitatively, using tools that can characterize the geometry and spatial properties of the patch or patches of mosaic, which depicts the forest loss and the changes in the temporal pattern. The aims of this paper are to observe the process of the forest fragmentation, to find out the changes of spatial patterns of habitat continuum by applying the spatial dynamics change analysis of the forest fragmentation phases, and to provide the comprehensive approach in determining the rapid change of the forest landscape structure in the spatial transformation process, based on the decision tree models. We find three phases of the forest fragmentation were identified, namely dissection, dissipation, and attrition. This study shows that the production forest area and a wildlife conservation area that contiguous or borders, has the same phases in the process of fragmentation of the forest, but both have a difference of the magnitude of forest loss. We find there are at least five effects of forest fragmentation to the landscape structure, those are increasing in a number of habitat patches, decreasing in a size of habitat patches, reduction in a habitat amount, increasing in a dispersion and interspersion of patch types, and reduction in a size of spatial connectedness between patches.Keywords: fragmentation, landscape metrics, spatial transformation.